2015
DOI: 10.1353/hsj.2015.0006
|View full text |Cite
|
Sign up to set email alerts
|

An Opportunity to Learn US History: What NAEP Data Suggest Regarding the Opportunity Gap

Abstract: The purpose of this study is to determine the degree to which Opportunity to Learn (OTL), is associated with students’ achievement in US History. Opportunity to Learn stems from the basic premise that there is an important relationship between the quality and frequency of classroom instruction and students’ levels of academic success. The authors examine National Assessment of Educational Progress in U.S. History (NAEP-USH) assessment data in order to better understand the relationship between classroom- and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 95 publications
4
39
0
Order By: Relevance
“…The unidimensional factor loading patterns were similar to previous analysis of NAEP-USH data (Heafner & Fitchett, 2015;Smith and Niemi, 2003). Conceptually, the factors aligned with existing literature surrounding students' learning of history.…”
Section: Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…The unidimensional factor loading patterns were similar to previous analysis of NAEP-USH data (Heafner & Fitchett, 2015;Smith and Niemi, 2003). Conceptually, the factors aligned with existing literature surrounding students' learning of history.…”
Section: Methodssupporting
confidence: 87%
“…However, those data were not available for the 2010 NAEP-USH. 6 Previous analysis (Heafner & Fitchett, 2015) indicates that this item was not significantly associated with NAEP-USH scores. For the sake of model parsimony, we did not include it in this study.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…In this investigation, boys outperformed girls on the TAKS Exit Level Social Studies Exam for the 2004-2005 to 2011-2012 school years. These results were consistent with researchers [5,17] who have also noted that boys have statistically higher scores on standardized exams in history. By analyzing each of the five objectives of the TAKS Exit Level Social Studies Exam, differences in social skills between boys and girls were also revealed.…”
Section: Connection With Existing Literaturesupporting
confidence: 93%
“…Boys also had statistically significantly higher test scores than girls on the Advanced Placement World History, European History, Government Politics U.S., and Psychology examinations in 2007 and 2011 [5] . In addition, Heafner and Fitchett (2015) [17] analyzed the National Assessment of Educational Progress of United States History and established that Grade 12 boys had statistically significantly higher test scores than Grade 12 girls on standardized United States History exams. Lastly, researchers [15,16] documented that boys had statistically significantly higher test scores on competency-based geography exams than girls.…”
Section: Introductionmentioning
confidence: 99%